High posterior tibial slope increases anterior cruciate ligament elongation in unicompartmental knee arthroplasty during early-flexion of lunge - Nan Zheng; Chunjie Xia; Huiyong Dai; Diyang Zou; Yubin Long; Zhiyong Hou; Qi Wang; Tsung-Yuan Tsai (BMC Musculoskeletal Disorders)
Abstract Background In-silico and in-vitro studies have revealed an appropriate posterior tibial slope (PTS) is critical for normal anterior cruciate ligament (ACL) and posterior cruciate ligament (PCL) tension and knee biomechanical behavior of unicompartmental knee arthroplasty (UKA). However, the effects of PTS on in-vivo elongation of ACL and PCL in UKA remains unknown. The study aimed to quantify in-vivo ACL and PCL elongations during lunge and analyze their relations with PTS. Methods Thirteen fixed-bearing (FB) and 11 mobile-bearing (MB) UKA patients were recruited. The postoperative medial PTS was defined as the angle between the tibial transverse plane (perpendicular to mechanical axis) and cut plane. Accurate knee spatial postures of UKA and contralateral native knees during single-leg lunge were measured by the dual fluoroscopic imaging system. The ACL (AM, PL bundles) and PCL (AL, PM bundles) footprints were determined based on anatomical features on femoral and tibial 3D surface model reconstructed from CT. A validated 3D wrapping method was used to measure ligament bundle length. The paired Wilcoxon signed-rank test was used to analyze the ligament elongation difference between bilateral knees. The Spearman correlation between PTS and average ligament elongation difference (ACL during 0–30° early-flexion, PCL during 60–100° deep-flexion) was calculated. Results The elongation of FB UKA PCL double-bundle was larger than contralateral sides in most flexion range of lunge (Max-Difference: AL 7.6 ± 8.7%, PM 8.2 ± 5.1%, p < 0.05). In contrast, ACL double-bundle elongations of MB UKA in mid-flexion were larger than contralateral sides (Max-Difference: AM 8.0 ± 8.1%, PL 7.6 ± 9.8%, p < 0.05). The increased PTS was significantly relevant to the increased ACL double-bundle elongation difference of bilateral knees for both FB and MB UKA patients (R > 0.6, p < 0.05). Conclusion There was abnormal in-vivo elongation of PCL in FB UKA and ACL in MB UKA during lunge and cause over-constraints to the contralateral knee. There was a positive correlation between PTS and ACL elongation difference for both FB and MB UKA, indicating excessive PTS should be avoided to preserve native ACL function in further UKA implantation. Levels of Evidence III.